Phenology and yield of native fruits cloudberry/bakeapple ( Rubus chamaemorus L.) and lingonberry/partridgeberry ( Vaccinium vitis-idaea L.) grown in Southern Labrador, Canada - Li, J.; Percival, D.; Hoyle, J.; White, J.; Head, K.; Pruski, K. (Canadian Journal of Plant Science, 2016)
Plant habitat, growth, fruit yield and occurrence of pollinators in cloudberry and lingonberry fields/bogs were monitored and analyzed at three locations in southern Labrador: Lanse’au Clair (51°41’ N, 57°08’ W), Red Bay (51°43’ N, 56°26’ W), and Cartwright (53°42’ N, 57°0’ W) over the two growing seasons, 2011 and 2012. The length of the growing seasons was 100–120 d ( DFRA 2014 ) with 600–700 growing degree days (GDD) ( AAFC 2014 ). The 2012 season was warmer than 2011. The plants recorded in belt transects belong to six families: Rosaceae, Ericaceae, Pottiaceae, Juncaeae, Equisetaceae, and Sphagnaceae. In the Ericaeae family, Vaccinium vitis-idaea, Arctostaphylos alpina, Empetrum nigrum, and Vaccinium angustifolium were found. In both seasons, the cloudberry was the first to bloom, followed by wild blueberry, lingonberry, and Labrador tea. The fruit yields of cloudberry and partridgeberry in southern Labrador were higher than those recorded in Finland, Norway, and in the USA. Pollinators were present in large numbers. Most of the specimens were from three orders: Hymenoptera, Diptera, and Lepidoptera. Temperature, precipitation, wind, and sunlight affected plant growth and the occurrence of pollinators. To our knowledge this is the most comprehensive study of plant growth, yield, and pollinators’ activity in cloudberry/partridgeberry fields conducted in Southern Labrador, Canada.